The Birds of Lembata (Lomblen), Lesser Sundas – Part 2 - Colin R Trainor (Indonesian Ornithologists’ Union, 2003)
Ornithological observations were made on the island of Lembata (Lomblen) over a l3 day period in December 2000, to increase knowledge of its poorly known avifauna. Only 58 species were known from previously published sources. Thirty-three additional species were recorded (a 70% increase), with a current total of 91 species (53 non-passerines and 38 passerines), including 73 residents, 15 Palearctic migrants and three austral migrants. The 33 new species for Lembata includes, among others, one raptor, lO Palearctic passage migrants and four forest birds. Four globally Threatened and Near Threatened species are present on Lembata (following Birdlife International 2001): the Critically Endangered Yellow-crested Cockatoo Cacatua sulphttrea, the Vulnerable Flores Green Pigeon Treron floris, and the Near Threatened Great-billed Heron Ardea sumatrana and Malaysian Plover Charadrius peronii. There are six Restricted-range species, all Lesser Sundas endemics, two additional Wallacean endemics and a total of 17 forest bird species. Biologically, Lembata is closely associated with Flores and other volcanic islands of the Inner Band a Arc; its avifauna is but a species poor subset ofFlores with every species recorded to date known also from that island.